Optimalisasi Perpustakaan Sekolah Di Smk Negeri 1 Baso Berdasarkan Standar Nasional Perpustakaan Sekolah Menengah Atas Nomor 12 Tahun 2017 - Gustina Erlianti; Sri Azizah (AL Maktabah, 2024)
The purpose of this study is to investigate how SMKN 1 Baso uses the school library as a learning resource. This study uses a descriptive methodology and is quantitative in nature. Perka No. 12 of 2017 concerning National Standards for Upper Middle School Libraries is the theory that was utilized to develop the indicators in this research. It contains five indicators that school libraries need to meet in order to become centers of learning for students. One hundred pupils from SMK Negeri 1 Baso served as samples for the investigation. The school library at SMK Negeri 1 Baso will be the research's outcome, and it will be based on the National High School Library Standard Number 12 of 2017, which has five indications, including: 1) Library Collection Indicator with a value of 2.58 categorized as Not Appropriate, 2) The Library Infrastructure Indicator with a value of 2.17 is categorized as Not Appropriate, 3) The library service indicator with a value of 2.83 is categorized as Sufficient, 3) The Library Personnel Indicator with a value of 2.32 is categorized as Not Appropriate, 4) The Technology Indicator Information and Communication with a value of 2.70 is categorized as Fair, so it can be concluded that the school library research variable has a total average value of 2.54, This indicates that the value is within the interval scale range of 1.8 < X ≤ 2,6 which means it can be classified into the not optimal/not good category.